Analysis Of the Effect of The Physical Properties of Liquids on External Forces (Factors) - A. B. Saparov; D. Jumamuratov; B B. Saparov; A. N. Karamov (Periodica Journal, 2022)
When a fluid flows, the coercive stress is created by internal friction forces. This property of a liquid depends on its type and temperature. The viscosity of a fluid decreases with increasing temperature in the rubbing surfaces. With a variable flow of liquid, a cavitation process can occur. The consequence of cavitation is the eurorosion of the material of the inner surface of the tubes, the sound phenomenon and the vibration of the installation. All this leads to reduced pressure, power and efficiency of the feed of the working machine. But cavitation is not always negative; it is used in a cavitation regulator. Therefore, when calculating, it is necessary to take into account the physical state and physical properties of the liquid. Of great importance is the observance of the temperature regime, especially at the junction of the working parts of the machines. when calculating the characteristics of cavitation, it is necessary to study the essence of cavitation in relation to the system under consideration
Keywords: Volumetric; Cohesion; Pressure; Temperature